2015
DOI: 10.1097/grf.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the Management of Endometrioma

Abstract: Endometriomas are common in reproductive-aged women, but controversy exists regarding their management. PubMed was searched to identify pertinent studies on outcomes of medical and surgical management of endometrioma, with focus on randomized controlled trials and meta-analyses. Surgical excision is more effective than fenestration/coagulation of endometrioma for pelvic pain but decreases antimullerian hormone. It may modestly improve the chances of spontaneous pregnancy, but does not impact chances of success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The best treatment for ovarian endometrioma-related pain symptoms is unknown and this has been prioritised as a knowledge gap by NVOG and the ESHRE Guideline Development Group ( NVOG 2016 ; Dunselman et al, 2014 ). A review from Johnstone and Link et al . (2015) included articles describing the effectiveness of hormonal therapy and surgery in patients with an ovarian endometrioma.…”
Section: Discussionmentioning
confidence: 99%
“…The best treatment for ovarian endometrioma-related pain symptoms is unknown and this has been prioritised as a knowledge gap by NVOG and the ESHRE Guideline Development Group ( NVOG 2016 ; Dunselman et al, 2014 ). A review from Johnstone and Link et al . (2015) included articles describing the effectiveness of hormonal therapy and surgery in patients with an ovarian endometrioma.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal treatment of endometriomas may be associated with cyst size reduction and symptom improvement but is unlikely to impart cyst resolution. [32][33][34][35][36][37] A recent meta-analysis has comprehensively reviewed the effect of medical management on ovarian endometrioma size and concluded that dienogest, oral contraceptive pills, gonadotropin-releasing hormone agonists, norethindrone acetate, and danazol have all been shown to reduce cyst diameter by a mean of 0.6-1.95 cm, with oral contraceptive pills having been studied most extensively and danazol showing the largest mean reduction in cyst size. 38 Medical management alone foregoes the opportunity for histologic diagnosis, and surgery is generally preferred for both diagnosis and treatment.…”
Section: Medical Managementmentioning
confidence: 99%